Pengaruh Jarak Tanam dan Takaran Pupuk Kandang Babi terhadap Pertumbuhan dan Hasil Kacang Tanah (Arachis Hypogaea L.) - Ludovikus Nono; Syprianus Ceunfin (Fakultas Pertanian, Universitas Timor, 2019)
Peanut is one of the legume plants that play an important role for food needs, but it has a high economic value so much that makes peanuts in addition to food as well as industrial materials. This study aims to determine the effect of plant spacing and pig manure dosage on the growth and yield of peanut plants (Arachis hypogaea L.). This research was conducted in December 2016 - March 2017 in experimental farm of Agricultural Faculty of Timor University, using Randomized Block 3 Factor 3 × 3 repeated. The first factor is spacing with three stages: Planting spacing 40 cm × 20 cm, spacing 40cm × 30 cm, and spacing 40 cm × 40 cm; the second factor is the dosage of pig manure with three levels namely: 0 t / ha, 5 t / ha, 10 t / ha. The results showed no interaction between the treatment of pig manure dosage with the treatment of plant spacing on all parameters of observation except on the root length parameter. Provision of pig manure with a dose of 10 t / ha yielded the heaviest dry weight per hectare (1.72 t / ha.) And significantly different from the control. Planting spacing of 40 cm × 40 cm yields the number of plant pods (20.37 pods), dry seeds per heaviest plant (60.97 g), and 100 heaviest seeds (40.93 g.). Keywords: Planting Spacing, Pig Manure, Arachis hypogaea L.